SOME ASPECTS OF FOREIGN TRADE OF UKRAINE IN THE CONTEXT OF EURO-INTEGRATION - Matveyeva, Viktoriya (Journal of European Economy, 2007)
The article analyzes the trade between Ukraine and the EU-27 based on trade interrelation and trade parity indicators. Proceeding from the research results, the author offers a classification of the EU countries based on their trade pattern with Ukraine, which in its turn laid the foundation for the recommendations aimed at further development of Euro-integration processes in the sphere of foreign trade. The author concludes that the expansion of foreign trade relations will foster the Euro-integration of Ukraine. However, trade orientation should be focused primarily on the countries interested in the mutual trade with Ukraine.